Analyzing the Effect of Need for Achievement and Locus of Control on Student Entrepreneurial Intentions - EKAWARNA EKAWARNA; YUSDI ANRA; QUROTTA AYUN; SERI ROMIOS; TARNAK TARNAK (Indonesian Research Journal in Education |IRJE|, 2020)
This study aimed to analyze the student entrepreneurial intentions model based on their psychological characteristics. More specifically, this study sought to explain whether the Need for Achievement (N-Ach) and Locus of Control (LoC) of students had an effect on Entrepreneurial Intentions (EI). An inferential research design with a cross-sectional study was adopted to collect the data. Students from faculty of teacher training and education, one public university in Jambi, were involved as the sample of the study. 63.14% of male students were selected by using a simple random sampling strategy, dominated by 81.78% of respondents aged less than 20 years. Data were collected through questionnaires and were analyzed by using the statistical correlation software and linear regression models to ensure the relationship between psychological characteristics and EI. The results indicated that there was a positive effect on psychological characteristics and EI on Student Entrepreneurial Intentions. N-Ach and LoC positively affected EI, both partially and jointly. Due to the limited instrument used in this study, only a self-reported questionnaire, which carried an opportunity for the response bias, and involved male students from a faculty in one public university in Jambi. Therefore, this model needs a further development through the incorporation of behavioral characteristics by involving larger samples allowing us understand on whether behavioral theories and traits are conflicting or complementary.